Effect of two different doses of oral midazolam premedication on separation anxiety in children scheduled for herniotomy - Olamuyiwa, Samuel B.; Aggo, Alfred T.; Johnson, Uyoata U. (International Journal of Scientific Reports, 2023)
Background: Peri-operative separation anxiety in children adversely impacts on their cognitive function and behavioural outcome. The aim of the study was to assess the effect of two different doses of oral midazolam premedication on separation anxiety in paediatric patients scheduled for herniotomy. Methods: Eighty-four eligible children aged 1-6 years, of American Society of Anesthesiologists (ASA) class I or II, scheduled for herniotomy, were randomized into two groups, A and B, of 42 each after ethical clearance and written parental consent. Children in group A and group B received 0.5 mg/kg and 0.75 mg/kg respectively of oral midazolam flavoured with paracetamol syrup, were observed, and later separated from parents at 30 min post-premedication. Premedicant acceptability was noted, and separation anxiety was assessed using the Richmond agitation sedation scale (RASS). Statistical significance was set at p<0.05. Results: All 84 children completed the study. At 30 min post-premedication, 47.6% in group A and 19.1% in group B had light sedation, while 52.4% in group A and 80.9% in group B were moderately sedated, p=0.0001. Premedicant acceptability and agitation scores between the groups were comparable, p>0.05. Conclusions: Oral 0.5 mg/kg and 0.75 mg/kg midazolam induced desirable sedation in children at the 30th min with comparable lower agitation scores; however, the 0.75 mg/kg dose achieved significantly faster onset and higher level of sedation in a greater proportion of the subjects.